2016
DOI: 10.4236/arsci.2016.42004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Food Restriction on the Uterus of Female Rats from the First and Second Generation

Abstract: Postnatal life is affected by changes in fetal development due to adverse events. The present study examined the effect of maternal food restriction on uterine structure and capacity in female rats from the first and second generations (FR1 and FR2) before and after puberty. Pregnant rats were fed ad libitum (Control, C) or maintained under food-restriction conditions (50%FR) during pregnancy. After delivery, all groups were given free access to food. Females from the first generation (FR1) were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Various experimental studies conducted on mice, rats, and pigs showed that many environmental and ethological prenatal stressors can have injurious effects on the pregnancy and early and long-term adverse effects on the offspring. Different prenatal treatments and stress types, such as medications [1], drinking water restriction and deprivation [2][3][4], feed restriction [5], immobilization [6,7], light intensity [8], stocking density [9], restraint or social stressors [10][11][12][13][14][15][16], heat or noise [17], to which a pregnant female is exposed, can affect pregnancy outcome and influence many aspects of physiological systems in the offspring including sexual behavior, puberty onset, gonad function, reproductive hormones, and development of the reproductive organs.…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental studies conducted on mice, rats, and pigs showed that many environmental and ethological prenatal stressors can have injurious effects on the pregnancy and early and long-term adverse effects on the offspring. Different prenatal treatments and stress types, such as medications [1], drinking water restriction and deprivation [2][3][4], feed restriction [5], immobilization [6,7], light intensity [8], stocking density [9], restraint or social stressors [10][11][12][13][14][15][16], heat or noise [17], to which a pregnant female is exposed, can affect pregnancy outcome and influence many aspects of physiological systems in the offspring including sexual behavior, puberty onset, gonad function, reproductive hormones, and development of the reproductive organs.…”
Section: Introductionmentioning
confidence: 99%